Developing the Brain towards Language Acquisition during Childhood from Age 2 to 10 a Systematic Review - Ghafar, Zanyar; Prastyo, Hari (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2023)
The early age is often recognized as the optimal period to start the acquisition of a foreign language. The optimal period for acquiring linguistic skills is during early life. Studying another language is the most efficient means of breaking beyond the limitations of just one language and culture. Moreover, gaining exposure to a different culture allows individuals to get a much deeper comprehension. Individually possessed. Hence, language acquisition may be seen as a valuable instrument for assimilating into a new culture and community. Learning a language entails acquiring knowledge about a different culture. Adolescent learners have high levels of motivation when it comes to acquiring a second language. The immature brain has remarkable plasticity, enabling it to readily acquire novel information. They possess a strong inclination to explore and understand the world surrounding them. The earlier we begin the greater the duration available for language exposure. The brain of young learners is sometimes referred to as a malleable brain. They have the ability to acquire knowledge without conscious awareness. Adults, in reality, have minds occupied with many concerns, whereas children's minds are focused on their lessons. In this study, we will discuss several benefits of early language acquisition. Studies indicate that the optimal period to teach fresh languages to a young kid is from birth to the age of 10. This review finding explores how children may acquire language more rapidly, have improved retention, and often have near-native pronunciation. Ultimately, this research emphasizes the benefits and drawbacks of acquiring a foreign language throughout infancy.